Incretin Effects and Enteral Feed Transitions - Ummu Kulthum, Jamaludin; Docherty, Paul D.; Preiser, Jean-Charles (Springer, 2014)
Critically ill patients are regularly fed with constant enteral nutrition infusions. However, the incretin effects of its impact on endogenous insulin concentration and secretion remains to be investigated. Many studies concluded the incretin effects are strongly driven by enteral feeding. This chapter deliberates current scenario in intensive care unit dealing with hyperglycemia which can be assisted by glycemic control protocol to prevent mortality and other adverse occurrences. Brief discussions on methodology consideration including enteral nutrition criterion and the identification of insulin sensitivity were included. Analyses based on the findings of glycemic control protocol with enteral feed-driven incretin effects were also highlighted to allow investigation on the incretin effect in critically ill patients via the changes in insulin sensitivity between feeding transitions. Although results have made distinct the incretin effect successfully, there are still limitations to the current study such as isolated gastrointestinal hormones. Thus, this chapter aims to aid clinicians and researchers to integrate this physiological effect into their current practice and applications in treating critically ill patients with hyperglycemia and other conditions. It also provides platform to design conclusive studies on incretin effect and to inform glycemic control protocol development and implementation in critical care.